Characterization of Horse-Spleen Ferritin as a Magnetic core-shell Nanoparticle - Kaur, Ravneet (My University, 2009)
Horse spleen Ferritin is characterized by X-ray diffraction, transmission electron microscope (bright field imaging and electron diffraction), differential thermal analysis, thermogravimetric analysis and vibrating sample magnetometer. Ferritin is found to be an almost spherical nanoparticle having size of about 8 nm and amorphous in nature. The core of the Ferritin decomposes at about 800 K. Ferritin is found to be antiferromagnetic at room temperature and its magnetic susceptibility at room temperature is about 6.0 × ^(10-4) emu / g Oe.
Keywords: Ferritin; Nanoparticles